Effect of Digital Marketing Strategies & Brand Image on University Selection by Students. Mediating Role of Perceived Value and Moderating Effect of Social Media - Raheem Ullah; Muhammad Arsalan Danish; Zahid Iqbal, (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2024)
The primary objectives of the study are to analyze how digital marketing strategies and brand image, influence students' decisions when selecting a university. Additionally, the study explores the mediating role of perceived value in the relationship between the independent variables and the dependent variable. Lastly, the research examines the moderating role of social media usage. A quantitative research design is employed, with data collected through a structured survey questionnaire distributed to 300 participants. The sample size consists of 300 participants selected using a convenience sampling technique. Data were collected through a structured survey questionnaire. Data analysis is conducted using SPSS and Smart PLS. The findings reveal that digital marketing strategies have a significant positive effect on university selection. Similarly, brand image plays a crucial role in shaping student preferences. The mediating analysis indicates that perceived value strengthens the relationship between digital marketing strategies, brand image, and university selection. Furthermore, social media usage is found to have a moderating effect, amplifying the impact of digital marketing strategies and brand image on university selection.